2008
DOI: 10.1111/j.1365-2044.2008.05490.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of head flexion on airway seal, quality of ventilation and orogastric tube placement using the ProSeal™ laryngeal mask airway*

Abstract: SummaryThis prospective self-controlled study was designed to evaluate the influences of head flexion on airway seal, quality of ventilation, and orogastric tube placement through the ProSeal TM laryngeal mask airway (ProSeal LMA TM ) in 80 anaesthetised, paralysed adult patients.After the ProSeal LMA was inserted and the cuff pressure was set at 5.9 kPa, ventilation quality, airway seal pressure, fibreoptic positions of the cuff and the drainage tube, orogastric tube placement and efficacy of intermittent pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…This lack of improvement may have been attributable to the fact that all patients showed adequate ventilation without leakage in the neutral position in our study, whereas 15% of the patients in a previous study showed obvious gas leakage with the Proseal LMA before moving from the neutral position. 8 Moreover, the discrepancy with our results regarding inadequate ventilation with the I-gel may be attributable to the noninflatable cuff of the I-gel, the smaller ventilating orifice area and the straighter shape of the airway tube compared with the air-Q SP airway. Our results showed that a higher inspiratory pressure is required in the flexed neck position to provide the same tidal volume as in the neutral position.…”
Section: Discussioncontrasting
confidence: 81%
“…This lack of improvement may have been attributable to the fact that all patients showed adequate ventilation without leakage in the neutral position in our study, whereas 15% of the patients in a previous study showed obvious gas leakage with the Proseal LMA before moving from the neutral position. 8 Moreover, the discrepancy with our results regarding inadequate ventilation with the I-gel may be attributable to the noninflatable cuff of the I-gel, the smaller ventilating orifice area and the straighter shape of the airway tube compared with the air-Q SP airway. Our results showed that a higher inspiratory pressure is required in the flexed neck position to provide the same tidal volume as in the neutral position.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast to all these findings, Xue et al . demonstrated excellent ventilation with Proseal Laryngeal Mask Airway in 80 (100%) adult patients in flexion compared to 68(85%) in the neutral position. They did not find any difference in the fiber optic score, expired tidal volume, and PIP with the change in head and neck positions.…”
Section: Discussionmentioning
confidence: 95%
“…One of the earlier studies was done by Xue and Mao et al [16] in which they evaluated the influences of head flexion on airway sealing pressure and quality of ventilation, through the ProSealTM laryngeal mask in 80 anesthetized adult patients. When compared to the neutral head position, the head flexed significantly improved the airway seal pressure and the quality of ventilation of the ProSeal LMA (p < 0.05) and they concluded that head flexion improved airway seal and ventilation quality of the ProSeal LMA.…”
Section: Discussionmentioning
confidence: 99%